Establishing a control system using QbD principles. Issue 5 (September 2016) - Kepert, J. Felix; Cromwell, Mary; Engler, Niklas; Finkler, Christof; Gellermann, Gerald; Gennaro, Lynn; Harris, Reed; Iverson, Raquel; Kelley, Brian; Krummen, Lynne; McKnight, Nathan; Motchnik, Paul; et al.
Abstract: Quality by design (QbD) is a global regulatory initiative with the goal of enhancing pharmaceutical development through the proactive design of pharmaceutical manufacturing process and controls to consistently deliver the intended performance of the product. The principles of pharmaceutical development relevant to QbD are described in the ICH guidance documents (ICHQ8-11). An integrated set of risk assessments and their related elements developed at Roche/Genentech were designed to provide an overview of product and process knowledge for the production of a recombinant monoclonal antibody. This chapter describes the elements and tools used to establish acceptance criteria and an attribute testing strategy (ATS) for product variants and process related impurities. The acceptable ranges for CQAs are set based on their potential impact on efficacy and safety/immunogenicity. This approach is focused on the management of patient impacts, rather than simply maintaining a consistent analytical profile. The ATS tools were designed to identify quality attributes that required process and/or testing controls, or that could be captured in a monitoring system to enable lifecycle management of the control strategy.